PAST, PRESENT AND FUTURES OF DISTRICT HEAT SUPPLIERS, WITH SPECIAL REGARD TO HUNGARIAN DISTRICT HEAT SUPPLIERS - LITERATURE REVIEW - SÜVEGES Gábor Béla (Annals of the University of Oradea: Economic Science, 2019)
In recent years, many researchers displayed interest in the different types of social innovations. In the current research, the author does not aim at creating a new definition, but at examining the possibilities to generate social innovations in the case of district heat suppliers by accepting the previously created definitions. In the case of district heat suppliers, three levels of social innovations can be distinguished and the current research aims at presenting how they have been realized worldwide for almost 140 years. Its methodology includes bibliography research based on seconder research methods and its result is a summary which helps make the heat supplier systems of different generations from the 19th-21st centuries transparent. The purpose of the present study is to examine the changes in the district heating systems of the world by examining international literature with the methods of literature review. District heating systems are grouped based on the following aspects: the role of heating systems in the given country, price level / price regulation, the technical and technological characteristics of heating systems and the share of renewable energy sources. The study emphasizes several times the related current conditions and characteristics in Hungary. The results of this literature review prove to be an important tool for the author’s further research.